Luteinizing hormone β‐subunit deficiency: Report of a novel LHB likely pathogenic variant and a systematic review of the published literature. (4th May 2022) - Barnabas, Rohit; Jadhav, SwatiRamteke; Arya, Sneha; Lila, Anurag Ranjan; Sarathi, Vijaya; Shah, Gaurang R.; Bhandare, Vishwambhar V.; Shah, Nalini S.; Kunwar, Ambarish; Bandgar, Tushar
Abstract: Context: Selective deficiency of β‐subunit of luteinizing hormone (LHB) is a rare disease with scarce data on its characteristics. Objectives: To describe a male with LHB deficiency and systematically review the literature. Design and Patients: Description of a male patient with LHB deficiency and a systematic review of LHB deficiency patients published to date (10 males and 3 females) as per PRISMA guidelines. Results: A 36‐year‐old Asian Indian male presented with infertility. On evaluation, he had sexual maturity of Tanner's stage 3, low testosterone (0.23 ng/ml), low LH (0.44 mIU/ml), high follicle‐stimulating hormone (FSH, 22.4 mIU/ml), and a novel homozygous missense likely pathogenic variant (p.Cys46Arg) in LHB . In the molecular dynamics simulation study, this variant interferes with heterodimerization of alpha‐beta subunits. Eleven males with pathogenic variants in LHB reported to date, presented at a median age of 29 (17–38) years, most commonly with delayed puberty. Clinical and biochemical profiles were similar to those of our patient. In the majority, testosterone monotherapy modestly increased testicular volume whereas human chorionic gonadotropin (hCG) monotherapy also improved spermatogenesis. In females, oligomenorrhoea after spontaneous menarche was the most common manifestation. Ten pathogenic/likely pathogenic variants (three in‐frame deletions, three missense, two splice‐site, one nonsense, and one frameshift variants) have been reported in nine index patients. Conclusion: We report a novel likely pathogenic LHB variant in an Asian Indian patient. The typical phenotype in male patients with LHB deficiency is delayed puberty with low testosterone, low LH, and normal to high FSH and hCG monotherapy being the best therapeutic option.